Influence of comprehensive physical rehabilitation on the restoration of motor deficiency in patients suffered ischemic stroke - Mishchenko, Valeriia K. (Psychiatry, Neurology and Medical Psychology, 2021)
The article consideres the issue of restoring lost motor function through comprehensive physical rehabilitation. The results of a study of 84 patients with cerebral ischemic stroke (CIS) are presented. The study of patients was conducted in the recovery period (from 3 to 6 months after the vascular accident). The average age of patients was 64.2±1.7 years. During the study all patients were divided into two groups depending on the type of rehabilitation treatment. The main group consisted of 43 patients who received standard medicines therapy aimed at secondary prevention (antihypertensive, hypocholesterolemic, hypoglycemic and other medicines), as well as therapy aimed at the correction and prevention of neurocognitive and dyscirculatory disorders (medicines with metabolic and vasoactive action) during the entire period of supervision. All patients of the main group underwent a course of comprehensive physical rehabilitation treatment. The latter included classes in kinesiotherapy, occupational therapy, speech therapy classes and, if necessary, patients received psycho-correctional and psychotherapeutic methods of treatment. The second (comparison) group consisted of 41 patients who received only drug treatment: standard basic therapy in the framework of secondary prevention of CIS and therapy aimed at the correction and prevention of neurocognitive, dyscirculatory disorders. The results of our study showed that the use of a comprehensive rehabilitation treatment program consisting of physical and medical methods are signifi cantly more eff ective for patients with motor disorders who have suff ered an ischemic stroke compared with the use of only drug therapy in these patients.